2004
DOI: 10.1002/ejic.200400025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Potassium Complexes Containing Terminal η2‐Pyrazolato Ligands

Abstract: The potassium complexes [K(η2‐3,5‐R2pz)(η6‐18‐crown‐6)] (R = Ph, tBu; pz = pyrazolato) were prepared by treatment of 3,5‐diphenylpyrazole or 3,5‐di‐tert‐butylpyrazole with potassium hydride in the presence of 18‐crown‐6. These complexes contain η6‐18‐crown‐6 and terminal η2‐pyrazolato ligands, and constitute the first examples of group 1 metal complexes with this pyrazolato ligand coordination mode. In contrast to [K(η2‐3,5‐Ph2pz)(η6‐18‐crown‐6)] and [K(η2‐3,5‐tBu2pz)(η6‐18‐crown‐6)], the aqua complex [K(η2‐3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The error of 0.3 Å is not acceptable in the comparison of X-ray analysis and recent density functional theory. However, we have noticed that typical KsO bond distances of potassium-containing complexes is 2.8 Å, 18,19 as seen in the adenine-binding site ( Figure 1). Arsenate reductase from Staphylococcus aureus involves the seven-coordinate potassium site: the K + ion is coordinated by seven oxygen atoms originated from Asn13, Ser36, Thr63, Asp65, and two water molecules (PDB ID 1JF8).…”
Section: Scheme 1: Adocbl-dependent Reaction Mediated By Diol Dehydramentioning
confidence: 93%
“…The error of 0.3 Å is not acceptable in the comparison of X-ray analysis and recent density functional theory. However, we have noticed that typical KsO bond distances of potassium-containing complexes is 2.8 Å, 18,19 as seen in the adenine-binding site ( Figure 1). Arsenate reductase from Staphylococcus aureus involves the seven-coordinate potassium site: the K + ion is coordinated by seven oxygen atoms originated from Asn13, Ser36, Thr63, Asp65, and two water molecules (PDB ID 1JF8).…”
Section: Scheme 1: Adocbl-dependent Reaction Mediated By Diol Dehydramentioning
confidence: 93%
“…It was suggested that this type of bonding should be common among Group 1 metal derivatives, and this was further supported by the subsequent isolation of the monomeric [K(η 2 ‐3,5‐Ph 2 pz)(η 6 ‐18‐crown‐6)] 7. Novel features of the potassium complexes include a case of π‐η 2 K coordination7 and examples of “slipped”, unsymmetrical η 2 binding, thus suggesting possible reversion to η 1 binding with the smaller Na + or Li + cations. Alternatively, if bridging prevails, the μ‐η 1 :η 2 :η 1 arrangement observed with potassium may be curtailed to the rare μ‐η 1 :η 2 mode, which has been observed only twice before 2g.…”
Section: Introductionmentioning
confidence: 94%
“…Although bridging coordination modes are still dominant in main‐group and d‐block transition‐metal pyrazolate complexes, recent advances in this field have found an increasing number of η 2 ‐coordinated complexes 3–5. 7, 8 The polynuclear potassium pyrazolato species obtained by Winter and co‐workers,2j [K(Ph 2 pz)(thf)] 6 , was the first structurally documented Group 1 complex to contain the η 2 pyrazolato coordination unit, which was incorporated into the then new μ 3 ‐η 1 :η 2 :η 1 arrangement. It was suggested that this type of bonding should be common among Group 1 metal derivatives, and this was further supported by the subsequent isolation of the monomeric [K(η 2 ‐3,5‐Ph 2 pz)(η 6 ‐18‐crown‐6)] 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] The difference in bond length may be due to interactions with the [18]crown-6 ligands. [18] The angles between the plane of the 1,2,4-diazaphospholide C 2 N 2 P core and the approximate plane of the six oxygen atoms of the [18]crown-6 ligand average 868.…”
Section: àmentioning
confidence: 99%